Napthalene diimide derivative based organic cocrystal frameworks as cathode electrodes for stable lithium batteries. (6th April 2023) - Zheng, Zihang; Ju, Zhengkun; Ma, Shuang; Liu, Zhiqi; Xiang, Wenxin; Chen, Jinqiu; Yang, Bo; Mu, Zifeng; Zhang, Jing; Li, Pan; Sheng, Peng
Abstract : A new type of organic eutectic cathode, which contains coronene and NDI derivatives in a highly-ordered void-rich packing manner, shows good specific capacity and cycle stability in LIB applications. Abstract : Two charge-transfer cocrystals using 1, 4, 5, 8-naphthalenetetracarboxylic diimide derivatives (NDIs) as donor block and coronene as acceptor segment were synthesized through solution centrifugation and investigated as cathode electrodes in lithium-ion batteries (LIBs). These cocrystals showed 1 : 1 mixed stacking with columnar structure, good thermal stability, and narrow band gaps of 2.24 eV or 2.34 eV. v ia alkyl terminal tuning, methyl-NDI based complex (CN-1) displayed lower binding ability than propyl substituted complex (CN-3) and could undergo a crystal transition into a new solvent-free phase with void-rich architecture. LIB based CN-1 cocrystal as cathode electrode showed a specific capacity of up to 230 mA h g −1 with long cyclability over 600 cycles due to its unique void-rich columnar and deformable structure. The lithiation and delithiation sites on aromatic backbones were testified by experimental and calculated results. This study thus not only provides a novel kind of organic cathode material but also proves that donor–acceptor complexes are promising candidates for the development of high-performance cathodes for LIBs.